FOREIGN BROKERAGE ACCOUNT REPLENISHMENT OPTIMIZATION MODEL - MORHACHOV, I.; GUMNENKOVA, Y. (Herald of Khmelnytskyi National University. Economic sciences, 2021)
In Ukraine, the stock market is still at the formation stage. On national stock markets, it is almost impossible to buy shares of world companies. Under such conditions, most individual investors-citizens of Ukraine work with foreign brokers. At the same time, the replenishment of foreign brokerage accounts by individual investors is carried out only by making a SWIFT payment, which is much more expensive than the cost of money transfers within the country. In such conditions, the current issue is the determination of the optimal amount of replenishment of the brokerage account at a foreign broker precisely for an individual investor - a citizen of the country. The purpose of the work is to clarify the theoretical and methodological provisions of the optimal replenishment of the brokerage account with a foreign broker for an individual investor - a citizen of the country. It is determined that the problem of optimizing the amount of replenishment of a brokerage account with a foreign broker for an individual investor - a citizen of the country rather lies in the plane of financial management. The article clarifies the theoretical and methodological issues of optimizing the amount of replenishment of a foreign brokerage account. A mathematical model is specified that allows you to quantify the optimal amount of replenishment of a foreign account by making a SWIFT payment. The model for optimizing the replenishment amount is based on the Wilson formula, while the types of expenses and losses that are optimized are determined. The methods of determining these expenses and losses were specified, and the presented model was tested according to the fees for making a SWIFT payment through Privatbank, as well as the average annual efficiency of investments in US corporations. The relevance of the presented model of optimizing the amount of replenishment of a foreign brokerage account is justified precisely for citizens of Ukraine. It was determined that for the average individual investor - a citizen of Ukraine, the optimal amount of replenishment of a foreign brokerage account (according to the size of the commissions of Privatbank and the average annual yield of US corporations over the past forty years) is an amount of 1000 US dollars. It is assumed that the investor immediately buys assets (only shares of US corporations) after replenishing the account. Investments in bonds, as well as the effectiveness of investments in bonds, were ignored.
Keywords: brokerage account replenishment optimization model; foreign brokerage account; Wilson formula; investment efficiency; alternative investment delay losses